Competing for What?: Linking Competition to Performance in Social Service Contracting - Meeyoung Lamothe; Scott Lamothe (The American Review of Public Administration, 2010)
This article explores the links between competition and contractor performance often assumed by market theory. Using data from Florida social service contracting, the authors test to see if competitively procured vendors outperform their noncompetitive peers regarding adherence to contract terms. It is found that, contrary to market theory, this is not the case. It is also found that district management capacity is positively related to performance and the performance of nonprofit vendors is indistinguishable from for-profits (whereas both appear to be outperformed by other government contractors). Finally, this study finds little evidence that performance or competition is related to the likelihood of maintaining contracts.
Keywords: competition; contract performance; management capacity